Bierni pisarze i wyrozumiali czytelnicy. Instytucja i interpretacja w polu badawczym antropologii literatury - Kopkiewicz, Aldona (Przestrzenie Teorii, 2013)
This essay presents a polemic against the anthropology of literature. The author examines the relation between the ethics of interpretation and the discourse of the anthropology of literature as well as cultural studies. She also shows theoretical conditions under which a textual subject appears to be weak and passive and thus becomes just a field in which a researcher can inscribe various cultural identities. In this way a researcher tries to restitute the subject after its poststructural “death”, but he/she might do that only by mediation through social and cultural identities, which he/she actually examines. On the practical level this entanglement causes a situation in which writers and artists create works that fulfill institutional expectations. It would be therefore necessary to establish to what extent an anthropological approach towards a text enables us to invent new models of subjectivity. Without this it would be difficult to consider literary/cultural studies to be a truly critical discipline based on independent, yet collaborative reflection to be found in theoretical and artistic texts alike.